Resilience of emerging market economies to global financial conditions - Turalay Kenc; Fatma Pinar Erdem; Ibrahim Unalmis (Central Bank Review (CBR), 2016)
With lessons learned from previous episodes as well as substantial improvements in economic policies and fundamentals over the years emerging market economies (EMEs) on average are better positioned to withstand financial turbulences, both now and in the near future, than in the past. Since their respective last financial crises most EMEs have been implementing more prudent policies, made stronger their governance frameworks and created financial safety nets as a buffer against adverse shocks. As a result, they were able to strengthen their stock and flow balances and policy frameworks, deepen local capital markets, and diversify their production and exports together with stronger global trade and financial linkages.
Keywords: 330; Emerging markets; Original sin; Financial crises